Impact of Pharmacist Counseling Strategy On Adherence And Knowledge of Chronic Kidney Disease Patients: Quasi-Experimental Assessment - Ulfa Filliana; Sholikhah Rosvita Oktasari; Sri Rahmat Molidia; Nanang Munif Yasin; Susi Ari Kristina (Academic Hospital Journal, 2026)
Background: Chronic kidney disease is a progressive condition that requires proper management to slow the decline in kidney function and reduce the risk of complications. Patients with low adherence have an increased risk of kidney progression, and knowledge level plays an important role in the treatment of kidney patients and in collaborative treatment decision-making. This study aims to evaluate the impact of a pharmacist counselling strategy on adherence and knowledge levels in CKD patients.Method: The method was quasi-experimental, with a pretest-posttest design, comparing the intervention and control groups. The intervention was carried out once a week for 1 month, using leaflets as a tool, with inclusion and exclusion criteria, among chronic kidney disease patients during September-October 2023.Result:  The study included 57 patients: 29 in the control group and 28 in the intervention group. The result showed that in the intervention group, there was an increase in knowledge, with a difference between pretest and posttest scores of Δ 8.79±7.802, compared to the control group, which showed a decrease in scores of Δ -0,49±4,932 (p=0.000). Adherence in the intervention group increased by Δ 2,71±1,822 compared to the control group, while adherence in the control group decreased by Δ -0,44±1,152 (p=0.000). A contributing factor to the patient's level of knowledge and compliance was duration of hemodialysis, p=0.032.Conclusion: The conclusion was that the pharmacist counselling strategy significantly improved CKD patient knowledge and medication adherence, and that the duration of hemodialysis significantly contributed to CKD patients' knowledge.